1992
DOI: 10.3892/ijo_00000002
|View full text |Cite
|
Sign up to set email alerts
|

Central review of cytogenetics is necessary for cooperative group correlative and clinical studies of adult acute leukemia: the Cancer and Leukemia Group B experience

Abstract: Abstract. The Cancer and Leukemia Group B has performed central review of karyotypes submitted by institutional cytogenetics laboratories from patients with acute myeloid (AML) and acute lymphoblastic (ALL) leukemia since 1986. We assessed the role of central karyotype review in maintaining accurate, high quality cytogenetic data for clinical and translational studies using two criteria: the proportion of karyotypes rejected (i.e. inadequate), and, among accepted (i.e. adequate) cases, the proportion of karyot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 0 publications
0
61
0
Order By: Relevance
“…Tables S1 and S8. Cytogenetic analyses were performed in CALGB/Alliance approved institutional laboratories and confirmed by central karyotype review (49), and the diagnosis of normal karyotype was based on ≥20 metaphase cells analyzed in BM specimens subjected to short-term (24 h or 48 h) unstimulated cultures. Molecular studies shown in Tables S1 and S8 were performed as described in SI Methods and Data and elsewhere (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Tables S1 and S8. Cytogenetic analyses were performed in CALGB/Alliance approved institutional laboratories and confirmed by central karyotype review (49), and the diagnosis of normal karyotype was based on ≥20 metaphase cells analyzed in BM specimens subjected to short-term (24 h or 48 h) unstimulated cultures. Molecular studies shown in Tables S1 and S8 were performed as described in SI Methods and Data and elsewhere (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cancer and Leukemia Group B report documented cases that were submitted as cytogenetically normal but, upon central karyotype review, were determined to carry such prognostically relevant chromosome aberrations as inv(3)(q21q26), inv(16)(p13q22), t(9;11) (p22;q23) or t(11;19)(q23;p13AE1) (Mró zek et al, 2004b). To further ensure that the karyotype is normal, some, but not all, studies subjected patient specimens to additional tests such as fluorescence in situ hybridisation (FISH) with a comprehensive set of genomic DNA probes capable of detection of the most relevant AML-associated genomic aberrations Döhner et al, 2005) or RT-PCR for the detection of fusion genes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Karyotypes were reported according to the International System for Human Cytogenetic Nomenclature 14 and karyotypes underwent central review. 15 Patients were divided into 4 groups: (1) CBF-AML [inv(16)(p13.1q22)/t(16;16)(p13.1;q22) and t(8;21)(q22;q22)]; (2) normal cytogenetics (CN-AML); (3) other abnormal karyotypes (excluding CBF-AML); and (4) unknown karyotype (due to inadequate mitoses).…”
Section: Cytogenetic Studiesmentioning
confidence: 99%